2022
DOI: 10.3390/atmos14010040
|View full text |Cite
|
Sign up to set email alerts
|

Planting Rice at Monsoon Onset Could Mitigate the Impact of Temperature Stress on Rice–Wheat Systems of Bihar, India

Abstract: The rice–wheat rotation is the dominant cropping system in Bihar, where food security of the rural population depends heavily on the production of rice and wheat. In Bihar, farmers plant rice after the first significant rains, and climatic shocks induced by low temperatures and terminal heat stress at the end of the corresponding season can significantly affect rice and wheat yields. The present work evaluates the benefit of using an earlier date for planting rice, following the monsoon onset, in reducing ther… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…In developing countries such as Bangladesh, smallholder farmers often have limited resources to cope with climate-related risks. However, management strategies such as shifting planting dates to minimize risks during critical growth stages can be a suitable approach that farmers are relatively able to act upon (Abdur Rashid Sarker et al 2013 ; Alam et al 2017 ; Sultan et al 2005 ), and that has been shown to mitigate risks (Balwinder-Singh et al 2019 ; Montes et al 2022 ). In Bangladesh, aman rice farmers tend to prepare their nurseries around mid to late June and wait for the first significant rainfall to prepare their field before transplanting roughly 25-30 days old seedlings.…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries such as Bangladesh, smallholder farmers often have limited resources to cope with climate-related risks. However, management strategies such as shifting planting dates to minimize risks during critical growth stages can be a suitable approach that farmers are relatively able to act upon (Abdur Rashid Sarker et al 2013 ; Alam et al 2017 ; Sultan et al 2005 ), and that has been shown to mitigate risks (Balwinder-Singh et al 2019 ; Montes et al 2022 ). In Bangladesh, aman rice farmers tend to prepare their nurseries around mid to late June and wait for the first significant rainfall to prepare their field before transplanting roughly 25-30 days old seedlings.…”
Section: Introductionmentioning
confidence: 99%